Writing and reading in Montessori preschools in the digital age – A valid teaching approach? - Per Gynther; Eva-Maria Tebano Ahlquist (Problemy Wczesnej Edukacji)
Writing and reading instruction in Montessori preschools remains consistent despite digital tools. In this article, the validity of Montessori’s reading and writing instruction is reviewed and discussed in relation to both previous research and societal changes influenced by technology. In conclusion, initial writing and reading instruction in Montessori preschools receives support from existing research, as it emphasizes sensory-motor experiences, including paper-and-pen activities. However, preschool children’s perspectives on the tools used for writing and reading instruction and the work they carry out in Montessori preschools have not yet been considered in research. Therefore, we suggest a need for further studies in order to better grasp the validity of her theory. Such studies could constitute an important contribution to the discussion about when and how writing by hand should be introduced within, as well as outside the Montessori community.